Child and adolescent sleep disturbances and psychopathology in a mental health clinic sample - Blacher, Aviva; McKenzie, Katarina N. A.; Stewart, Shannon L.; Reid, Graham J. (Frontiers in Sleep, 2024)
Introduction: Children and adolescents treated in specialty mental health services are more likely to have sleep disturbances than those without mental health problems. Few studies have investigated the relationship between sleep and psychopathology in broad clinical samples of children. We examined the relationship between sleep disturbance and age on internalizing and externalizing psychopathology in a sample who sought treatment at children's mental health centers. Methods: Secondary data analyses were completed on a sample of children (N=13,472; aged 4 to 18; 55% male) from 39 children's mental health agencies in Ontario, Canada, who completed a semistructured assessment, the interRAI Children and Youth Mental Health (ChYMH). A split-half sample approach was utilized (S1 n = 6,773, S2 n = 6,699). Hierarchical regressions examined the effects of sleep disturbances (i.e., difficulty falling asleep, staying asleep, night waking, bedtime resistance, falling asleep during the day) on internalizing and externalizing symptoms, above and beyond established child-(i.e., age, sex, sensory sensitivity, pain) and family-level variables (family functioning, caregiver distress, parenting strengths). Age was tested as a moderator for sleep disturbances on both outcome variables. Results: Overall, 6.7% of children had clinically significant sleep disturbance scores (≥10 out of 16) on the interRAI ChYMH. In both samples, sleep disturbances predicted internalizing (S1 ΔR 2 = 10%, S2 ΔR 2 = 10%) and externalizing symptoms (S1 ΔR 2 = 2%, S2 ΔR 2 = 1%), above and beyond child and family variables. Age moderated the relationship between sleep disturbances and internalizing symptoms (S1 ß = 0.07; S2 ß = 0.07; ΔR 2 = 0.004 in both samples), but not externalizing symptoms; sleep disturbance was more strongly related to internalizing symptoms amongst adolescents (ß =.98) than children (ß =.62). Discussion: The relationship between sleep and internalizing symptoms appears to change as children move through development. Further, sleep was a stronger predictor of internalizing problems in adolescents than children, suggesting an additional focus of clinician efforts in this age group. These findings strengthen the importance of routine assessment of sleep, as is done with the interRAI ChYMH.